Linguistic capacity was present in the Homo sapiens population 135 thousand years ago - Miyagawa, Shigeru; DeSalle, Rob; Nóbrega, Vitor Augusto; Nitschke, Remo; Okumura, Mercedes; Tattersall, Ian (Frontiers in Psychology, 2025)
Recent genome-level studies on the divergence of early Homo sapiens, based on single nucleotide polymorphisms, suggest that the initial population division within H. sapiens from the original stem occurred approximately 135 thousand years ago. Given that this and all subsequent divisions led to populations with full linguistic capacity, it is reasonable to assume that the potential for language must have been present at the latest by around 135 thousand years ago, before the first division occurred. Had linguistic capacity developed later, we would expect to find some modern human populations without language, or with some fundamentally different mode of communication. Neither is the case. While current evidence does not tell us exactly when language itself appeared, the genomic studies do allow a fairly accurate estimate of the time by which linguistic capacity must have been present in the modern human lineage. Based on the lower boundary of 135 thousand years ago for language, we propose that language may have triggered the widespread appearance of modern human behavior approximately 100 thousand years ago.